Application of computational fluid dynamics (CFD ) to the study of venturi-type geometries for hydrodynamic cavitation production (Revista Cientifica Ingenio Magno, 2020)
Cavitation is a hydrodynamic effect, represented in the release of high amounts of energy, the product of the abrupt depressurization of a fluid mass and causing highly interesting and beneficial phenomena in various fields of engineering, due to the multiple physical and chemical properties it presents. Taking into account the above, this research studied the effects that the different geometric (diameters, angles and lengths) and physical (pressure, speed and number of cavitation) parameters could have on the attainment of cavitation. This was done by simulating twelve different geometries (performed in AutoCAD) in the commercial software ANSYS Fluent 19.0. Finally, high cavitational activity was obtained when a type III geometry (length of 1 mm and divergent angle of 7.5o) is used under an initial pressure of 10 atmospheres.
Keywords: Cavitation; Computational Fluid Dynamics; Water Purification